Ramadan Fasting and Kidney Stones: A Systematic Review: Ramadan Fasting and Kidney Stones - Amjadi, Mohsen; Soleimanzadeh, Farzin; Ghamatzadeh , Hamidreza; Hajebrahimi, Sakineh; Hosseinifard, Hossein; Salehi Pourmehr, Hanieh; Tahmasbi, Fateme (Urology Journal, 2020)
Purpose: Ramadan fasting in Muslims may contain several hours of abstaining from food and drinking in any kind. This can potentially increase the risk of urinary stone disease. Current literature on possible effects of Ramadan fasting on urolithiasis is rather limited. Having the gap in scientific background, we decided to evaluate the available comparative information in this systematic review. Materials and Methods: We included all studies comparing fasting and non-fasting conditions, studies evaluating stone formation and clinical manifestations of kidney stone disease. All the English studies published from January 1980 to the end of 2019 were included. The exclusion criteria were as followed: fasting out of Ramadan, non-comparative studies, animal studies, patients with bladder stones, and studies evaluating conditions that are only indirectly related to the stone formation or clinical manifestations of it. Applying the Joanna Briggs Institute (JBI) methodology for systematic review showed the quality of included studies was not high. Results: Only five studies remained after exclusion. Meta-analysis was not applicable due to the diversity in methods and evaluated population. Conclusion: Main trend of the included studies is toward showing no difference between fasting and non-fasting conditions in terms of renal stone formation. However, generalization of the findings to greater populations should be applied carefully considering the heterogeneity of results and quality of studies.